2017
DOI: 10.1111/1468-0009.12277
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Response to an On‐Shelf Nutrition Labelling System in Supermarkets: Evidence to Inform Policy and Practice

Abstract: This study demonstrates support for policies promoting on-shelf nutrition labels designed according to evidence-informed principles, but policymakers should move forward with caution when investing in such systems until research has confirmed optimal label design, clarified the mechanisms through which dietary intake is improved, and assessed associations with nutrition-related health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 31 publications
2
83
4
1
Order By: Relevance
“…Successful efforts in this direction can follow the path of the American Heart Association’s Heart-Check Program, which has driven part of the fast-food industry to meet nutrient quality standards [ 23 , 24 , 25 ]. Additionally, a mark label for traditional Mediterranean foods and recipes might facilitate a better adherence to this dietary pattern when making food choices, comparable to the Guiding Stars system in Canada, which observed better food-purchasing patterns and measurable nutritional benefits [ 57 ]. Information on websites, blogs, books, health-related resources, and cooking magazines can promote the MedDiet for Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Successful efforts in this direction can follow the path of the American Heart Association’s Heart-Check Program, which has driven part of the fast-food industry to meet nutrient quality standards [ 23 , 24 , 25 ]. Additionally, a mark label for traditional Mediterranean foods and recipes might facilitate a better adherence to this dietary pattern when making food choices, comparable to the Guiding Stars system in Canada, which observed better food-purchasing patterns and measurable nutritional benefits [ 57 ]. Information on websites, blogs, books, health-related resources, and cooking magazines can promote the MedDiet for Americans.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in findings for the number of SOBF present, and the proportion displaying the HSR, indicate that examination of differences in product availability between the Australian States and Territories is needed. This is important because most Australian studies assessing attributes of supermarket environments to date have been conducted in Sydney and Melbourne [ 71 ], and findings may not translate to other metropolitan areas within Australia.…”
Section: Discussionmentioning
confidence: 99%
“…However, widespread use of a single, effective FoPL is likely to have the greatest impact on product selection. For example, supermarket studies using a star-based rating system applied to shelf tags across all products found a shift toward increased purchases of healthier foods [ 28 30 ]. Other supermarket studies using the MTL did not observe any shift in purchases, however this may have been due to the label not being applied across all products [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%